Could catchment conservation be funded through urban water tariffs? A case study of three South African cities - du Plessis, Nicola (Department of Biological Sciences, 2023)
Water scarcity is a global issue that has traditionally been addressed by over-abstracting surface water and constructing more dams. However, these solutions are environmentally destructive and, in some cases, insufficient to meet future water demands. To secure future water supply, it is necessary to invest in the protection and restoration of catchment areas which have become degraded due to human activities. In many developing countries, catchment management is financed solely by public funding, which is often insufficient to cover the costs of catchment conservation. Supplementary funding sources thus need to be investigated to ensure the future success of these interventions. This study aimed to address whether household water tariff pricing could be used as a mechanism for securing funds for catchment restoration. The objectives of the study were to (i) elicit households' willingness to pay (WTP) for water, (ii) determine factors influencing WTP, and (iii) investigate whether aggregate revenue generated from households' WTP at the municipal scale could cover the costs needed for catchment conservation in that water service provider region. Household surveys were conducted on 1244 households in three coastal metropolitan municipalities in South Africa: the City of Cape Town, Nelson Mandela Bay, and eThekwini. Contingent valuation revealed that average WTP for water across all three municipalities was R540 per household per month, 4.6% more than what households currently pay for water. Factors that significantly influenced WTP included income, age, household size, municipality, and satisfaction with municipal service delivery. Based on the WTP for 11 income categories, aggregate WTP for water amounted to R5.94 billion per year for the City of Cape Town, R5.83 billion per year for eThekwini, and R1.26 billion per year for Nelson Mandela Bay municipality. This translated to a positive consumer surplus of R1.2 billion for the City of Cape Town and R826 million for eThekwini, which is approximately three times greater than the estimated budgets required to cover the costs to restore both of the catchment areas supplying water to these municipalities. Since WTP for water was lower than the amount that residents currently pay in Nelson Mandela Bay, water pricing cannot be considered a mechanism to finance catchment conservation for this municipality. Choice models further revealed that households were willing to pay 34% more than their current water bill to avoid water restrictions, and 22% more to secure water supply through more environmentally sustainable options. These results demonstrate the importance of context and scale when making water investment and pricing decisions over the longer term.